1 and 2 Chronicles as a discourse of power - Geyser-Fouché, Ananda (HTS teologiese studies, 2023)
This article reflected a comparison of 1 and 2 Chronicles with its source documents. It transpires that the history of Israel and Judah is selectively retold by the authors of Chronicles with deliberate omissions and additions reflecting a certain emphasis. While the northern kingdom is negatively portrayed, the southern kingdom is positively evaluated. David is idealised as the perfect king. He is credited with founding the religious cult, which is contradicting the view in Exodus. The Jerusalem temple cult is legitimised and asserted as representing the only accurate religion. Chronicles 1 and 2 secured the temple elite’s position by legitimising their actions, functioning in this community as a discourse of power for as long as the (second) temple existed. Being a discourse of power, it set margins and excluded various groups usually considered part of the people of YHWH. The destruction of the (second) temple led to the disempowerment of this text, opening the way for it to be included in the Hebrew canon. The key insights of this article were that 1 and 2 Chronicles were used as a discourse of power, but the power block was lifted once the second temple was destroyed.Contribution: This article fitted into the scope of the journal by using historical-critical methods but also concepts from poststructuralism, namely the concept of powers behind texts and in language.